ANALYSIS FACTORS INFLUENCING UTILIZATION OF INFORMATION TECHNOLOGY AND ITS IMPACT ON USER SATISFCATION AND MANAGERIAL PERFORMANCE (Study of an Information Technology based University in Surabaya) - Tanuwijaya, Haryanto (Accounting Department,, 2021)
Purpose — This research was conducted to explore factors influencing utilization of information technology and its impact on user satisfaction and managerial performance. Design/methodology/approach — This research is a quantitative explanatory research using primary data collected by questionnaire. The respondents were fully structural officer in the tecnology information based university. Data analysis uses structure equal modeling with SmartPLS.Findings — The results of this reseach indicate that the social, affection, complexity, long term consequences factors have a positive and significant impact toward utilization of information technology. Job fit and facilitating condition factors have no significant to utilization of information technology. This study result also indicates that utilization of information technology has no impact to managerial performance. Practical implications — To enhance managerial performance, the institution should find another approach in the utilization of information technology. The increasing of education business competition in digital era requires institution to utilize information technology appropriately in order to gain the top and superior university.Originality/value — This study can be used as a recommendation for the insitution related policies of utilization and invesment of information technology in the future to gain managerial performance. Keywords — Social, Affection, Complexity, Job fit, Long term consequences, Facilitating condition, Utilization of information technology, User satisfaction, Managerial performance. Paper type — Case study